Desenvolvimento de competências e habilidades do século 21 por meio de jogos digitais: uma experiência com Minecraft na reconstrução virtual da cidade de Mariana/MG - Lara, Carla Luczyk Torres (2019)
This research aims to investigate how adolescents are learning the "4Cs" of 21st century skills and abilities (communication, collaboration, creativity and innovation, critical thinking and problem solving) as a means of creating virtual worlds using the Minecraft game. What justifies this investigation is that although some scholars understand that games can be valuable tools of simulation and reflection on different aspects of daily life, there has been a shortage of research on the insertion of games in schools with reflective meaning and, therefore, there is a need research in technologies in education, in the field of digital games. What motivates the realization of this research is the possibility of investigating alternatives that can contribute to the debate about the insertion of games of creation of virtual worlds in the school. The present investigation seeks to answer the following problematizing questions: a) What do teenage "players" learn by working in a videogame environment? b) How can participants apply these skills in the real world? C) How do adolescent "players" apply strategies and collaborate to solve problems while working in a videogame environment? d) How do participants apply strategies to help themselves in a video game environment? The theoretical approach and review of previous studies related to the proposed theme focused on topics related to 21st century competencies and skills. We opted for the methodology of scientific research of a qualitative nature, of the descriptive type, with origin of bibliographical / field. The instruments of data collection are questionnaires, interviews and observation. The context of this investigation involves eight adolescents from basic education who contributed to the virtual reconstruction of the city of Mariana / MG, using the Minecraft game